2012
DOI: 10.1039/c2jm35650c
|View full text |Cite
|
Sign up to set email alerts
|

A facile and effective method to prepare long-persistent phosphorescent nanospheres and its potential application for in vivo imaging

Abstract: In order to prepare new promising optical nanoprobes, long afterglow nanospheres with a narrow size distribution were successfully synthesized using mesoporous silica nanospheres (MSNs) both as morphology-controlling templates and the silicon source of long afterglow silicate. In our experiments, metal ions (Sr 2+ , Mg 2+ , Eu 3+ , Dy 3+ ) were impregnated into the pores of mesoporous silica nanospheres followed by high temperature calcination. The X-ray powder diffraction results show that SrMgSi 2 O 6 crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…[25] Briefly, 7 mL of ethanol, 0.2 g of CTAB, and 50 μL of diethanolamine were dissolved in 25 mL of water under stirring at 60 °C for 30 min to prepare a transparent solution. Then, 2 mL of tetraethoxysilane were added rapidly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Briefly, 7 mL of ethanol, 0.2 g of CTAB, and 50 μL of diethanolamine were dissolved in 25 mL of water under stirring at 60 °C for 30 min to prepare a transparent solution. Then, 2 mL of tetraethoxysilane were added rapidly.…”
Section: Methodsmentioning
confidence: 99%
“…[ 24 ] We speculate that homogeneous distribution of these reactants in confi ned mesoporous nanostructures results in a higher reactivity than would otherwise be the case; such phenomena were observed previously. [25][26][27][28][29]…”
Section: Formation Of Mzgc By Using Msns As Nanoreactors Morphology Amentioning
confidence: 99%
“…Since their emissions are in the region of the biologically transparent window (650-1100 nm) [12,13], moreover, since the emission lifetime is sufficiently long to permit late time-gated imaging, long persistent phosphors (LPPs) are unique and superior to other labels [14][15][16][17][18]. In such a case, auto-fluorescence from tissue organic components during imaging can be completely avoided, which gives rise to an extraordinary high signal-to-noise ratio [19,20].…”
Section: Introductionmentioning
confidence: 97%
“…The variation of surface area, pore volume and pore size is induced by the micelle aggregation of surfactant CTAB, which was reported in previous studies. 39, 40 In addition, it was found that, under the excitation using 980 nm NIR laser, three narrow-band emission peaks at ~ 478 nm, ~ 650 nm and ~ 800 nm presented for all three samples. (Fig.…”
mentioning
confidence: 90%